Genome-wide characterization and stress-responsive expression analysis of the cinnamoyl-CoA reductase gene family in soybean - Li, Xin; Li, Yunlong; Li, Sinan; Sun, Minghao; Cai, Quan; Sun, Yan; Li, Shujun; Yin, Yue; Yu, Tao; Zhang, Jianguo (Frontiers in Plant Science, 2025)
BackgroundCinnamoyl-CoA reductase (CCR) catalyzes the first step in lignin biosynthesis and is crucial for plant development and stress response. Although CCR genes are characterized in many plants, a complete analysis of the soybean CCR family and its response to abiotic stress is limited.MethodsWe identified soybean CCR genes genome-wide using bioinformatics. Phylogenetics, gene structures, motifs, chromosomal distribution, and synteny were analyzed. Promoter regions were checked for cis elements. Expression patterns were studied across tissues and under four abiotic stresses (salt, alkaline, drought, and osmotic) using transcriptome data.ResultsFifteen CCR genes (GmCCR1-GmCCR15) were identified in the soybean genome, distributed across 12 chromosomes. Phylogenetic analysis revealed two major subfamilies with distinct evolutionary origins. The genes encode proteins ranging from 269 to 363 amino acids, with predicted subcellular localization mainly in the Golgi apparatus. Motif analysis identified 10 conserved domains, showing subfamily-specific distribution patterns. Promoter analysis uncovered abundant hormone-responsive and stress-related cis-elements, including abscisic acid response elements (ABRE), methyl jasmonate-responsive elements, and drought-responsive elements. Transcriptome analysis demonstrated tissue-specific expression patterns, with higher levels in roots, stems, and developing seeds. Under abiotic stress conditions, five genes (GmCCR1, GmCCR4, GmCCR7, GmCCR8, and GmCCR15) were significantly upregulated, while three genes (GmCCR2, GmCCR11, and GmCCR13) were downregulated or showed no response. Notably, GmCCR4 exhibited the most dramatic changes in expression across all stress treatments, with peak upregulation occurring 3 hours post-treatment.ConclusionsThis analysis explores soybean CCR gene evolution, structure, and divergence. Identifying stress-responsive CCR genes, especially GmCCR4, highlights a target for improving soybean stress tolerance via molecular breeding or genetic engineering. These findings enhance understanding of lignin regulation under stress and support the development of climate-resilient soybeans.